The Evaluation of Flow-Mediated Vasodilation in the Brachial Artery Correlates With Endothelial Dysfunction Evaluated by Nitric Oxide Synthase Metabolites in Marfan Syndrome Patients - Lomelí, Oscar; Pérez-Torres, Israel; Márquez, Ricardo; Críales, Sergio; Mejía, Ana M.; Chiney, Claudia; Hernández-Lemus, Enrique; Soto, Maria E. (Frontiers in Physiology, 2018)
Marfan syndrome (MS) is of the most common connective tissue disorders. Although most patients have mutations in the fibrillin-1 gene (FBN1) and more than 1,700 mutations have been described, there are no mutations in less than 10% of patients. Aortic dilation is the most important complication; it involves chronic inflammatory processes and endothelial dysfunction. Prospective study from March 2015 to January 2017, in a cohort of 32 patients of MS confirmed by Ghent criteria and 35 controls of both genders, with a median age of 26 years (18-56). Patients had no comorbidities such as diabetes, hypertension and/or neoplasms. They were not being treated with statin, NSAIDs, calcium antagonists, oral nitrates and/or beta-blockers during seven days prior to the study and patients with smoking history in the last 4 years. Controls were matched by age and gender. We analyzed endothelial dysfunction by flow-mediated vasodilation in the brachial artery, determining the maximum peak flow in the reactive hyperemia phase with a Philips Envisor device with Doppler capability. Its correlation with serum levels of biological markers that could participate in endothelial dysfunction pathways such as NO3–/NO2– ratio, NO2-, citrulline, TNFα, IL-1, IL-6, IL-10, IL-8, osteopontin, ICAM, VCAM and NO3–/NO2– was determined. Endothelial dysfunction was found in 21 MS patients (65%). The aortic annulus (AAo) was of 27 mm (22-40) and 24 mm (22-30) (p=0.04) in MS patients with and without dysfunction. The level of NO3–/NO2– ratio, was of 108.95 ± 12.05 nM/ml in controls vs. 170.04 ± 18.76 nM/ml in MS (p=0.002), NO2– was of 33.78 ± 3.41 nM/ml vs. 43.95 ± 2.59 nM/ml (p=0.03), citrulline 62.65 ± 3.46 vs. 72.81 ± 4.35 μMol/ml, (p=0.06). VCAM median was 39 pg/ml (0-86) vs. 32 pg/ml (11-66) (p=0.03), respectively. The correlation of VCAM with triglycerides (TG) was of 0.62 (p=0.005). There were no differences in TNFα, IL-1, IL-6, IL-8; IL-10 and osteopontin. MS endothelial dysfunction is related to aortic diameters, and increased levels of VCAM, L-citrulline and NO3–/NO2– ratio, NO2–. VCAM-1 has a significant correlation with TG and could play a significant role in endothelial dysfunction.